A Facile Method to Prepare Defect‐Sealed Zeolitic Imidazolate Framework Membrane on Cu Net for Gas Separation. Issue 29 (7th September 2022) - Guo, Biao; Xu, Ruisong; Wang, Tonghua; Liu, Jinxuan
Abstract: A direct method is reported for the preparation of zeolitic imidazolate framework (ZIF) membrane on Cu net without any surface modification technologies. The synthetic mechanism can be attributed to the in situ formed Cu‐N interlayer serving as the nucleation sites, which promote the growth of ZIF membrane. The dense polycrystaline membrane shows moderate H2 /CH4 separation performance comparable to previous reports. To further eliminate membrane defects, polymer/MOF suspension instead of pure polymer can be used to accurately seal the valley among crystalline grains. As a result, the as‐prepared composite membrane with highly exposed crystal surface shows enhanced H2 /CH4 selectivity of 71.0 with little loss in H2 permeance. Abstract : Without surface modification, the in situ formed Cu‐N interlayer on the Cu net can directly serve as the nucleation sites, promoting the growth of dense zeolitic imidazolate framework. For better separation performance, the "valley" on the membrane surface can be accurately sealed with polymer‐MOF suspension.